The trickle‐down effect of managers' belief in the importance of human resource management practices on employee performance: evidence from China. (1st June 2022) - Jiang, Jianwu; Li, Shuling; Zhu, Wenbo
Abstract : Many studies have investigated the effects of human resource management practices on employee performance. Managers' belief in the importance of competent human resource management at the firm level and the department level influences its impact on employee performance, yet this has not been examined. Accordingly, based on the theory of upper echelons, this study empirically tested a trickle‐down effect model of managers' belief in HRM importance on employee performance. A cross‐level analysis was conducted using data collected from 56 top managers, 91 department supervisors and 316 employees in China. The results showed: (1) top managers' belief in human resource management importance positively influenced human resource management competence, which, in turn, played a fully mediating role between human resource management importance at the firm level and human resource management effectiveness at the departmental level; (2) the effectiveness of human resource management as evaluated by department supervisors exerted a significant positive influence on employees' human resource practices; and (3) the effectiveness of human resource management as evaluated by department supervisors indirectly affected employees' performance through their perceived human resource practices.